2015
DOI: 10.1002/2015ja021302
|View full text |Cite
|
Sign up to set email alerts
|

Global features of the disturbance winds during storm time deduced from CHAMP observations

Abstract: A wind‐driven disturbance dynamo has been postulated many decades ago. But due to the sparseness of thermospheric wind measurements, details of the phenomena could not be investigated. In this study we use the CHAMP zonal wind observations from 2001 to 2005 to investigate the global features of the disturbance winds during magnetically disturbed periods. The disturbance zonal wind is mainly westward, which increases with magnetic activity and latitude. At subauroral region, the westward zonal wind is strongly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
94
3

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 64 publications
(103 citation statements)
references
References 64 publications
6
94
3
Order By: Relevance
“…According to previous studies, the time‐integrated merging electric field ( E m ) can be expressed as Em(t,τ)=t1tEm(t)e(tt)/τdtt1te(tt)/τdt, where Em is treated as a continuous function of time t, t 1 is chosen 3 h before the actual epoch, and τ is the e ‐folding time of the weighting function in the integrands, with a value τ = 0.5 h. Richmond et al [] found that it is appropriate to consider the past 3 h of solar wind variations. An e ‐folding time of 0.5 h was also found suitable for calculating the merging electric field in previous ionospheric studies [ Xiong et al , ; Xiong and Lühr , ; Xiong et al , ].…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…According to previous studies, the time‐integrated merging electric field ( E m ) can be expressed as Em(t,τ)=t1tEm(t)e(tt)/τdtt1te(tt)/τdt, where Em is treated as a continuous function of time t, t 1 is chosen 3 h before the actual epoch, and τ is the e ‐folding time of the weighting function in the integrands, with a value τ = 0.5 h. Richmond et al [] found that it is appropriate to consider the past 3 h of solar wind variations. An e ‐folding time of 0.5 h was also found suitable for calculating the merging electric field in previous ionospheric studies [ Xiong et al , ; Xiong and Lühr , ; Xiong et al , ].…”
Section: Resultsmentioning
confidence: 84%
“…During active periods enhanced energy input into the thermosphere at high latitudes on the nightside will cause density bulges, which propagate to middle and low latitudes, via traveling atmospheric disturbance, and or enhanced equatorward wind. The equatorward winds, increasingly turning westward toward middle and low latitudes owing to the action of Coriolis force, need 3–4 h to propagate to equatorial regions [ Fujiwara et al , ; Ritter et al , ; Xiong et al , ]. As shown in Figure c, the westward disturbance wind is most prominent during 00–06 MLT after Δ t = 4.5 h. In fact, this enhanced westward disturbance wind explains well the eastward disturbance electric field on the nightside, as shown in Figure b.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…If the DD is indeed the explanation for these observed enhanced flows, then there are two things to note. First, it does not appear until 11 h after the onset, a longer time than the 3 to 6 h delay reported by other researchers [ Balan et al ., ; Tulasi Ram et al ., ; Xiong et al ., ]. It is possible, as argued by Tulasi Ram et al .…”
Section: Equatorial Ionosphere Responsementioning
confidence: 96%
“…The input of enhanced solar wind and magnetospheric energy can alter physical and chemical characters of the ionosphere-thermosphere system due to their dynamical coupling, further leads to an ionosphere and thermosphere storm (Buonsanto, 1999). Meanwhile, the energy input at the auroral or subauroral regions heats the thermosphere and drives equatorward neutral winds and traveling atmospheric/ionosheric disturbances (e.g., Huang et al, 2012;Ritter et al, 2010;Xiong et al, 2015). Meanwhile, the energy input at the auroral or subauroral regions heats the thermosphere and drives equatorward neutral winds and traveling atmospheric/ionosheric disturbances (e.g., Huang et al, 2012;Ritter et al, 2010;Xiong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%